30‐Day Postoperative Outcomes Following Transcervical Zenker's Diverticulectomy in the Elderly: Analysis of the NSQIP Database. (8th December 2020) - Moroco, Annie E.; Saadi, Robert A.; Patel, Vijay A.; Lehman, Erik B.; Gniady, John P.
Abstract : Objective: To compare the effect of patient factors, including age, on 30‐day postoperative outcomes and complications for patients undergoing transcervical Zenker's diverticulectomy. Study Design: Retrospective cross‐sectional analysis. Setting: American College of Surgeons National Surgical Quality Improvement Program (NSQIP) Database. Methods: Patients who underwent open Zenker's diverticulectomy ( Current Procedural Terminology code 43130) were queried via the NSQIP (2006‐2018). Outcomes analyzed include patient demographics, medical comorbidities, admission type, operative characteristics, length of admission, postoperative complication, readmission, and reoperation. Results: A total of 614 patients were identified. Mean age at time of surgery was 71.1 years, with 13.4% older than 85 years. Outpatient procedures were performed in 29.8%. Postoperative complications occurred in 6.7%, with reoperation and readmission rates of 6.4% and 7.2%, respectively. A mortality rate of 0.3% was observed. Only smoking status (odds ratio, 2.94; P =. 008) and history of congestive heart failure (odds ratio, 10.00; P =. 014) were shown to have a significant effect on postoperative complications. Conclusion: Smoking status confers a high risk for postoperative complication. Age was not an independent risk factor associated with adverse outcomes following open diverticulectomy, suggesting this procedure can be safely performed in patients with advanced age.